Annual population dynamics of mango fruit flies (Diptera: Tephritidae) in West Africa: socio-economic aspects, host phenology and implications for management. (25th April 2014) - Vayssières, Jean-François; Sinzogan, Antonio; Adandonon, Appolinaire; Rey, Jean-Yves; Dieng, Elhadj Oumar; Camara, Koumandian; Sangaré, Morodian; Ouedraogo, Sylvain; Hala, N'klo; Sidibé, Adama; Keita, Youssouf; Gogovor, Guy; et al.
Abstract : Introduction . Losses in West African commercial mango orchards due to fruit fly infestations have exceeded 50% by the middle of the crop season since 2005, resulting in considerable income loss for the growers.Materials and methods . In 2009, weekly monitoring of adult fruit fly species of economic significance was carried out in eight West African countries at 12 sites across five agro-ecological zones: (i) Humid Forest, (ii) Guinean savanna, (iii) Southern Sudan, (iv) Northern Sudan, and (v) Sahelian. Trapping was performed using methyl eugenol and terpinyl acetate in 288 Tephri-traps, targeting Bactrocera invadens and Ceratitis cosyra .Results . The data showed that B. invadens was present throughout the year in the Forest zone, abundant for 7 months, with a peak in May at the end of the mango season, C. cosyra being totally absent. In the Guinean savanna zone, B. invadens was abundant for 6-7 months, with a peak at the beginning of June coinciding with the season, with a few C. cosyra . In the Southern Sudan zone, B. invadens was abundant for 6 months, with a peak in mid-June during the season, C. cosyra peaking in April. In the Northern Sudan zone, B. invadens was abundant for 5 months, with a peak at the end of June at the end of the season, C. cosyra peaking in May. In the Sahelian zone, B. invadens was abundant for 4 months, peaking in August during the season, C. cosyra peaking just before. These preliminary results showed that the exotic species, B. invadens, was present at high levels [mean peak of 378 flies per trap per day (FTD)] in all agro-ecological zones, while the native species, C. cosyra, preferred the drier zones of West Africa, with lower population levels (mean peak of 77 FTD).Conclusion . Detection trapping of male flies with parapheromones is a useful indicator of field population levels and could be used to deploy control measures (IPM package) in a timely manner when the Economic Injury Level is reached. Control strategies for these quarantine mango fruit fly species are discussed with respect to agro-ecological zones and the phenological stages of the mango tree.